LOGO REDESIGN AS PART OF "LAMITA" DIGITAL BRANDING STRATEGY IN ORDER TO REACH THE ZOOMERS - Radhitanti, Asri; Kusumawati, Yudhistya Ayu; Arindiono, Rudi Yulio; Mirana, Adonia (SEEIJ (Social Economics and Ecology International Journal), 2025)
In the context of digital branding activities, it is crucial to ensure that the fundamentals of branding are well established from the beginning. Numerous studies on the effectiveness of logos as brand identities in branding have demonstrated that well-established logos significantly enhance brand awareness. In order to reinforce Lamita's brand awareness among the Zoomers, or Generation Z (Gen Z) as a qualified ethnic accessories artisan from Malang city, the research team initially provided assistance with the redesign of the logo. The objective of this strategy is to ensure that the visual representation of the logo effectively conveys the essence of Lamita's qualifications, while aligning more closely with the preferences of Gen Z. It is anticipated that the logo redesign programme will provide the necessary foundation to implement a more optimal digital branding strategy for Lamita, thereby increasing brand awareness amongst the targeted consumers and facilitating purchase decisions, ultimately leading to economic independence for Lamita. The paper provides a detailed description of the process undertaken to redesign the logo through the Community Based Research method.